The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/s0100-736x2017001000019
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa de Mycoplasma em aves da família Psittacidae mantidas em diferentes cativeiros no Brasil Central

Abstract: RESUMO: O presente estudo teve como objetivo investigar a presença de Mycoplasma gallisepticum e M. synoviae em diferentes espécies de psitacídeos cativos no Brasil Central. Um total de 300 amostras foram coletadas e corresponderam a 41 espécies de psitacídeos da fauna brasileira, provenientes do CETAS, criadouro comercial e criadouro conservacionista. Quatorze espécies apresentaram amostras positivas para M. gallisepticum destacando a maracanã-verdadeira (Primolius maracana) (01/02, 50%), a arara-canindé (Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
2
4
1
Order By: Relevance
“…The results found for Psittaciformes contrast the studies of Silva et al (2016) and Carvalho et al (2017) when assessing the presence of Mycoplasma spp. in asymptomatic parrots under human care.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…The results found for Psittaciformes contrast the studies of Silva et al (2016) and Carvalho et al (2017) when assessing the presence of Mycoplasma spp. in asymptomatic parrots under human care.…”
Section: Resultscontrasting
confidence: 95%
“…Silva et al (2016), when analyzing 85 parrots of different species from a zoo in Pernambuco, reported the presence of Mycoplasma spp. in 16.47% of the birds, however these mycoplasmas were not identified as MG or MS. Carvalho et al (2017), when evaluating 300 samples of CETAS parrots, commercial and conservation breeding, observed positivity for M. gallisepticum (MG) in 21.6% (16/74) in CETAS, 15.7% (19/121) in commercial breeding, and 6.7% (7/105) in conservationist, while for MS the occurrences were 2.7 % (2/74) in CETAS, 0.0% (0/121) in commercial breeding and 1.9% (2/105) in conservationist. MG was still described with a high occurrence by Gomes et al (2010) in parrots from the seizure of trafficking with the positivity of 85.4%.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of mycoplasmas in asymptomatic wild captive birds has already been reported in the study by Silva et al (2016) who observed a prevalence of 16.5% Mycoplasma spp. in 85 parrots and Carvalho et al (2017) who found percentages of 21.6%, 15.7% and 6.7% positivity in birds from, respectively, a Wild Animal Sorting Center, a commercial breeding site and a conservation breeding site and these results agree with what was found in our study. The presence of these free-living ducks close to captive birds in the zoo can pose a risk to health of susceptible birds and to species in recovery programs, since there is a possibility that Muscovy ducks are acting as reservoir of pathogenic mycoplasmas.…”
Section: Occurrence Of Avian Mycoplasmas In Free-living Muscovy-duckssupporting
confidence: 93%
“…Therefore, there was no evidence of susceptibility to Chlamydophila infection in the bird species included in the present study. Carvalho et al (2017) also observed the absence of speciesspecific predisposition to infection by a variety of pathogens (e.g. Mycoplasma gallisepticum, and M. synoviae) in captive psittacids in Goiás State, Brazil.…”
Section: Resultsmentioning
confidence: 81%